Rod fracture and related factors after total en bloc spondylectomy - Park, Se-Jun; Lee, Chong-Suh; Chang, Bong-Soon; Kim, Young-Hoon; Kim, Hyoungmin; Kim, Sang-Il; Chang, Sam-Yeol (The spine journal, 2019)
Several studies have reported favorable oncosurgical outcomes after total en bloc spondylectomy (TES) for treatment of primary malignant tumors or oligometastatic tumors. Considering that TES is indicated for patients with longer life expectancy, long-term instrumentation-related issues such as rod fracture needs to be addressed. To investigate delayed rod fracture and related factors after TES. Multicenter, retrospective study. Thirty-two patients who survived for more than 2 years after TES. Rod fracture and related factors. The relationships between rod fracture and related factors were investigated using Kaplan-Meier survivorship analysis with log-rank test. The analyzed factors were sex, age (<60 or ≥60), tumor histology (primary or metastatic), location of resected tumor (thoracic [above T11], thoracolumbar [cases including T12-L1], or lumbar [below L2]), number of resected vertebrae (1, 2, or 3), anterior support method (expandable cage, mesh cage, or strut bone graft), rod diameter (5.5 mm or 6.0 mm), and history of radiotherapy including preoperative or postoperative radiotherapy. The study population consisted of 18 men and 14 women, with a mean age of 49.0 years. Nineteen patients had primary tumors and 13 patients had metastatic tumors. The mean follow-up duration was 49.8 months (range, 24–166 months). Twelve of 32 patients (37.5%) experienced rod fractures at an average of 29.2 months (range, 8–93 months) after TES. Of these 12 patients, 8 underwent revision surgery caused by back pain aggravation (n = 7) or nonunion on computed tomography scan (n = 4). Location of resected tumor and history of radiotherapy were significantly associated with rod fracture (p = .004 and p = .019, respectively). Rod fracture was not a rare complication after TES surgery. History of radiotherapy and TES at lumbar level were significant risk factors related to rod fracture. A robust strategy to obtain solid osseous fusion should be considered when planning TES.